Performance of Two-Hop Relay Assisted Decode-and-Forward Transmission under Mixed Fading Environments - Kapucu, Nuri; Bilim, Mehmet; Develi, Ibrahim; Kabalci, Yasin (Elektronika ir Elektrotechnika, 2015)
This study analyses the performance of two-hop decode-and-forward (DF) relaying protocol under mixed faded channels by evaluating outage probability ( ) and average bit-error probability (ABEP). It is assumed that the channel between source and relay is Rayleigh fading, whereas the relay-destination link is subject to Weibull fading. First, a closed-form expression is formulated for and then it is used to obtain ABEP for the considered system model. The ABEP performance of two-hop DF relaying is presented for M-ary phase shift keying (M-PSK) signaling with different constellation sizes. Moreover, the proposed analytical expressions are verified by simulations that present the correctness of the derived formulas. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.9806